(untitled) (International Journal of Engineering and Computer Science, 2018)
In this paper we calculate the cost of software product using Empirical study. Early prediction of software cost and quality is important for better software planning and controlling. In early development phases, design complexity metrics are considered as useful indicators of software testing effort and some quality attributes. Although many studies investigate the relationship between design complexity and cost and quality, it is unclear what we have learned from these studies, because no systematic synthesis exists to date. Referring to the famous statement of Tom DeMarco , “You cannot control what you cannot measure”. Quality Measurements are – as in any other engineering discipline – also in software engineering a cornerstone for both improving the engineering process and software products. Quality Measurement not only helps to visualize the abstraction of software development process and product but also provide an infrastructure to perform comparison, assessment and prediction of software development artifacts. The large part of software measurements is to, in one way or another, measure or estimate software complexity and quality due to its importance in practices and research. The relationship between cognitive complexity and software external quality depends on comprehending ability of software developer, tester or maintainer. This factor is not deterministic and hence, cannot be investigated any other ways than empirically. In order to improve quality an organization must take into account the costs associated with achieving quality since the objective of continuous improvement programs is not only to meet customer requirements, but also to do it at the lowest cost. This can only happen by reducing the costs needed to achieve quality, and the reduction of these costs is only possible if they are identified and measured. Therefore, measuring and reporting the cost of quality (CoQ) should be considered an important issue for managers. Risk management is the identification, assessment, and prioritization of risks followed by coordinated and economical application of resources to minimize, monitor, and control the probability and/or impact of unfortunate event or to maximize the realization of opportunities. Risk management’s objective is to assure uncertainty does not deviate the endeavour from the business goals.